A modelagem de leitores e de leituras no discurso midiático da revista nova escola - Ana Charnizon (2008)
This research investigated readers and reading modelling inserted in Nova Escola magazine media speech, based on Faircloughs Critical Discourse Analysis theoretical-methodological pretext. The magazines supposed reading image, and how it builds up a reader model with specific beliefs, ideologies and values, was investigated. Data compilation involved editorial and graphic project analysis of two issues published in 2006 and a semi-structured interview with a journalist who was part of the team. Nova Escola, it was verified, intends to reach a slice of readers which includes educators and teachers who teach at elementary and high school levels. The graphic project analysis provided evidence of the intention to propose panoramic readings of the texts and their order on the support as a way to produce effects on the way of reading. Readers modelling also occurs when the reader is pushed to create dispositions so he can act with the goal to improve Brazilian education; when there is imposition of the neoliberal perspective on education which leads to enterprise restructuring of the pedagogical goals and functions of the subjects implied in the educative process; when the problematizer dimension of the pedagogic activity, the scientific data brought in to the text and teachers work conditions are erased. The inquirer tone is replaced by the language of New Journalism, which seeks to make fiction out of facts and seduce by the narratives warm tone. The texts analysis shed light upon the significant presence of a discursive trend characterized by the power assimetry breakage in which the editor tries to establish an accomplice relationship through informational and conversational speech, achieving, thus, the hierarchy between producers and readers. Finally, discursive strategies were verified which favour the construction of the Fundação Victor Civita ethos and which also favour the credibility and legitimacy of what is published in Nova Escola. This research, following the critical-transforming path of Fairclough, revealed how important it is to realize the fact that a publication can manipulate its readers and build identities from values and ideologies which are inherent and subtle to the mediatic speech. Through the speech mechanisms consciousness of certain media powers-that-be, readers can act in a way to affect such hegemonic ideological formations to make them not only being reproduced, but also altered through discursive practices restructuring.